Management techniques for elasmobranch fisheries (FAO, 2005)
This publication describes the scientific principles and techniques used for resource management of elasmobranch fisheries with emphasis on the particular context of elasmobranchs. The management characteristics of these fishes are described - their common bycatch character and their biological constraints on productivity (low growth rate, late maturity and low fecundity). Stock assessment of elasmobranchs is described in the context of management objectives in a wide management context. Special attention is given to accurate species identification given the prevalent aggregating of landings data across species, genera and often families in this group. Techniques and experiences for tagging elasmobranchs for population estimation are described as well as methods of genetic techniques for stock identification.